Family, lifestyles and new and old type of smoking in young adults: insights from an italian multiple-center study - La Fauci, V.; Mondello, S.; Squeri, R.; Alessi, V.; Genovese, C.; Laudani, N.; Cattaruzza, M. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Tobacco smoke is the epidemic of modern times due to its tremendous burden of diseases and deaths, greater than that produced by alcohol, AIDS, drugs, road accidents, murders and suicides combined. In Italy, 26% of the population smokes and the high prevalence of smoking even among young people is crucial for the Tobacco Industry, because young people are the reservoir which replaces smokers who quit or die. The aim of this study is to investigate smoking habits and determinants of smoking among young adults.Methods. This cross-sectional study enrolled young people from three Italian regions: Latium (central Italy) Calabria (southern Italy) and Sicily (the largest Italian island). An anonymous, multiple-choice online questionnaire was distributed through social networks. Questions investigated individual habits and lifestyles (smoking, alcohol and coffee consumption, physical activity), the presence of smokers in the family and the use of electronic cigarettes. Descriptive and multivariate analyses were used to describe the characteristics of the sample and to evaluate factors associated with smoking status. All statistical analyses were conducted in SAS software version 9.4 (SAS Institute Inc., Cary, NC, USA). All hypothesis tests were 2-tailed and p values